High-frequency Repetitive Transcranial Magnetic Stimulation (rTMS) Accelerates onset Time of Beneficial Treating Effects and Improves Clinical Symptoms of Depression - Dai, Lilei; Wang, Peng; Du, Hui; Guo, Qingshan; Li, Fen; He, Xinfu; Zou, Shaohong (CNS & Neurological Disorders - Drug Targets, 2022)
Background: In recent years, more and more patients with depression demonstrate suicidal intention and suicidal behavior. Objective: To evaluate the effectiveness of repetitive transcranial magnetic stimulation (rTMS) in treating depression with suicidal ideation. Methods: Eighty-nine depression patients with suicide intention were administrated drugs combined with four weeks of Active rTMS (n=40) or sham (n=49) rTMS treatment. The 24-item Hamilton Depression Rating Scale for Depression (HAMD-24) and Self-rating Idea of Suicide Scale (SIOSS) were used to evaluate suicide risk and depression severity at baseline, weeks 2 and 4. A 25% reduction in HAMD-24 score from baseline was defined as treatment response. More than a 20% reduction in HAMD-24 score from baseline within the first 2 weeks of treatment was defined as an early improvement. Results: No statistical significance was found for baseline sociodemographic and illness characteristics between the two groups (P >0.05). There was a significant difference for HAMD-24 and SIOSS scores between the two groups at weeks 2 and 4. Active rTMS group demonstrated a more significant score reduction compared to the Sham rTMS group at weeks 2 and 4. There was a significantly greater number of patients with early improvement observed in the Active rTMS group compared to those in the Sham rTMS group at weeks 2 (P <0.05). There was a significant difference in responder rates between the two groups at weeks 4 for HAMD-24 scores (P <0.05). Conclusion: rTMS could accelerate the onset time of beneficial treating effects and improve clinical symptoms of depression. During the treatment course, cognitive disorder, sleep disorder, anxiety/ somatization, retardation, and hopelessness symptoms were improved dramatically, and suicidal ideation was reduced.
Keywords: cognition